PENGARUH KONSENTRASI GULA KRISTAL Dan ASAM SITRAT TERHADAP KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK SIRUP AIR KELAPA - Marwanto, Marwanto Marwanto (Jurnal Sains dan Teknologi Pangan, 2016)
Coconut is a versatile crop, since all parts of the coconut beneficial to human life. Coconut water contains nutrients that is good enough then it has the potential to be processed into drinks and syrups from coconut water. Citric acid is widely used in industry, especially the food industry, beverages, and pharmaceuticals. Granulated sugar is crystallized sugar cane liquid. Usually white but some are brown (raw sugar). The purpose of this study was to use coconut water waste by processing as a syrup. This study used completely randomized designed in factorial design consisting of the first factor of white crystal sugar/sugar cane (G) which consists of three levels ie. 55% (G1), 60% (G2) and 65% (G3) and the second factor of acid citrate (S) consisting of two levels ie 0.2% (S1) and 0.3% (S2). The results showed that the best analysis of viscosity test is 0,018 Nm-2 sec and the water content is 38.25% while glucose content is 49.254% while the organoleptic test consisting of aroma, taste and viscosity very significant effect on color but produce no real effect.